Media Disruption Impact on Journalists' Integrity: A Role Study of Independent Journalists Alliance (AJI) in Maintaining Press Integrity and Freedom - Fauzi, Mahmud Ikhsan; Abidin A, Zainal; Claretta, Dyva (Universitas KH. Abdul Chalim Mojokerto, 2025)
Digital transformation in the media industry has created structural disruption that has significantly affected the integrity of journalists' work, especially in the dimensions of accuracy, independence and compliance with ethical codes. This research aims to analyze digital media disruption impact on the integrity of journalists in Surabaya, as well as exploring the role of Surabaya Independent Journalist Alliance (AJI) in maintaining the values of journalistic professionalism amidst complex structural pressures. Using a qualitative-descriptive approach and data collection techniques through in-depth interviews and documentation studies, this research highlights Independent Journalist Alliance (AJI)'s four main roles: as an ethical values keeper through membership selection, as a facilitator of professional education, as an internal ethics supervisor, and as an advocate for legal and digital protection for journalists. The discovery shows that Independent Journalist Alliance (AJI) functions as a normative actor capable of intervening in digital disruption through community-based institutional strategies and value solidarity. By referring to Disruptive Innovation theory and Mediatory Theory of the Message, this study concludes that the sustainability of journalism integrity does not only depend on individual agency, but also on the existence of institutions that are able to stabilize value in a media ecosystem driven by algorithmic and market logic.